root of sec square tita +cosec square tita = tan tita +cot tita prove
Answers
Answered by
6
Heya friends.
from LHS
√sec²¢+cosec²¢
➡√1+tan²¢+1+cot²¢...{• ° •sec²¢=1+tan²¢
and cosec²¢=1+cot²¢}
√tan²¢+cot²¢+2...
now,
(tan¢+cot¢)² =tan²¢+cot²+2tan¢×cot¢
(tan¢+cot¢)²=tan²¢+cot²¢+2----1)
so, from 1) at the place of cot²¢+tan²¢+2 we can say that (cot¢+tan¢)²
now in question
=>√(tan¢+cot¢)²
=tan¢+cot¢ ..Rhs prooved here
Hope it helps you
@Rajukumar@@@☺☺
from LHS
√sec²¢+cosec²¢
➡√1+tan²¢+1+cot²¢...{• ° •sec²¢=1+tan²¢
and cosec²¢=1+cot²¢}
√tan²¢+cot²¢+2...
now,
(tan¢+cot¢)² =tan²¢+cot²+2tan¢×cot¢
(tan¢+cot¢)²=tan²¢+cot²¢+2----1)
so, from 1) at the place of cot²¢+tan²¢+2 we can say that (cot¢+tan¢)²
now in question
=>√(tan¢+cot¢)²
=tan¢+cot¢ ..Rhs prooved here
Hope it helps you
@Rajukumar@@@☺☺
smffathu:
tq
Similar questions
Environmental Sciences,
9 months ago
Physics,
9 months ago
Math,
1 year ago
India Languages,
1 year ago
English,
1 year ago
Hindi,
1 year ago